Stochastic Petri Net simulation modeling of a campus evacuation process (2017)
"This project is focused on understanding the individuals-psychology during an evacuation process. For this, an individual is modeled with his/her most relevant characteristics an then, the individuals are categorized in groups by their similarities and their emergent evacuation behaviors. This behaviors, given the emergency situations, are translated into a given set of rules for each individual to decide the optimal route to his/her evacuation. Once the parameters, variables and processes are defined, the next step is to model the system using the petri nets approach. This approach requires certain model-s logic, which is established through the definitions of the individuals for each group, and the algorithms associated to the decision-making process and evacuation process. Thus, the basis for the simulation model of the evacuation of the entire campus for future works is established."--Tomado del Formato de Documento de Grado